Cerebral Infarction Due to Polycythemia Vera: A Case Report - Oktasari, Nur Aida; Nurotus Saniyah (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Changes in blood viscosity can cause thrombosis in the brain, causing a stroke. Polycythemia vera is one of the causes of blood hyperviscosity. This study aimed to present cases of cerebral infarction related to polycythemia vera. Case presentation: A 55-year-old woman came to the emergency room with complaints of sudden weakness in the left limbs. One week before admission, the patient complained of headaches accompanied by spinning dizziness. Her left limbs often tingled and became weaker. There was an asymmetric facial deviation to the right, and the patient had difficulty communicating with unclear articulation. Specific examination of neurology shows dysarthria, left-sided motor type facial paralysis, examination of motor strength of the upper and lower extremities on the left 2 and 5 on the right, and the left upper limb often feels tingling. On the left limb, normal physiological biceps reflex was found, positive Chaddock pathological reflex. Morphological examination of peripheral blood showed normocytic normochromic with erythrosis and thrombocytosis and found giant platelets. This patient was diagnosed with an ischemic stroke caused by cerebral infarction, with polycythemia vera etiology, and accompanied by comorbid diseases of diabetes mellitus and uncontrolled hypertension. Conclusion: In patients with high-risk criteria for thrombosis, the management of phlebotomy, administration of low-dose aspirin, and cytoreduction in the form of hydroxyurea aims to achieve a hematocrit <45% so as to prevent worsening and recurrence of stroke.